Screening Parameters of Transfusion-Transmitted Infection using Rapid Diagnostic Method - Gravinda Widyaswara; Aulia Rahman; Prilly Layyinatunnisa; Maria Regina Sepe; Rosadelima Dagaina Koten; Zakia Tanzila; Syofianis; Delia Irjayanti Tamu Apu (Indonesian Journal of Biology Education, 2024)
Blood transfusions are an important part of medicine for patient recovery. Therefore, the transfused blood must be free from viruses, bacteria, and even parasites that can be transmitted through blood transfusions. Human Immunodeficiency Virus (HIV/AIDS), Hepatitis C, Hepatitis B, and Syphilis are among the illnesses that can be transferred through blood transfusions. This research aims to determine screening parameters for transfusion-transmitted infection using the rapid diagnostic test method. This type of research is experimental with a cross-sectional design. The samples used were ten blood samples, taken intravenously and then centrifuged at a speed of 1300 rpm for 4 minutes. After that, screening is carried out with a rapid diagnostic test. The screening results of the ten blood samples examined were valid and negative or non-reactive for HIV/AIDS, Hepatitis C, Hepatitis B, and Syphilis. These results indicate that the blood samples tested can be categorized as blood samples that passed the screening test or the blood examination test for four parameters of transfusion-transmitted infection.